DECENTRALIZATION OF SCHOOL-BASED EDUCATION AND MANAGEMENT TOWARDS THE SOCIETY ERA 5.0 - Abdul Halim Ade; Firman; Riska Ahmad (Yayasan Citra Dharma Cindekia, 2021)
The presence of technology and information today has really brought about a big change in aspects of human life where almost all of life is associated with digital use. The era of the industrial revolution 4.0 which was felt to be unresolved, but was surprised again by the presence of a new era, namely society 5.0. Life in the era of society 5.0 which is believed to also affect all aspects of life, including the education aspect. Teachers as the spearhead of education strive to be able to create superior students and be able to compete with existing changes. However, the efforts of teachers tend not to get maximum results if they are not supported by policies that provide flexibility for teachers to develop all the potential in students. One of the policies that can support teachers in carrying out their duties properly is the implementation of decentralization in the education line and implementing school-based management (SBM), so that they can build and develop new concepts in education management, such as how to manage, organize education, develop resources. human resources for the better.